Optical Response of Various Heavy Metal Ions-Based Carbon Dots Photoluminescent Quenching Effect - Sugiarto, Iyon Titok; Yulianto, Nursidik; Tresna, Wildan Panji; Lewa, Ismira Wahyu Lestari; Isnaeni, Isnaeni (Diponegoro University Semarang Indonesia, 2023)
Carbon nanodots (Cdots) are a type of semiconductor carbon-based nanomaterial that is gaining popularity due to its excellent characteristics (e.g., biocompatibility, unique optical properties, low cost, eco-friendly, and high stability). In terms of physicochemical properties for an environmentally friendly sensor application, this material also has an excellent ability to detect heavy metal ions in the biosphere. In this study, we proposed a comprehensive optical characterization to examine the sensitivity of the Cdots probe for three heavy metal ions (i.e., Mn, Pb, and Cr ions) and compare the performance. The results of the experiment revealed that each heavy metal ion reacted differently to the physical properties of Cdots. With the addition of Cr, Mn, and Pb metal ions from the original Cdot solution, which is only 1.45 ns, the lifetime of quenched Cdots is 2.55 ns, 3.15 ns, and 2.15 ns, respectively, according to the TRPL experiments. With additional Cr, Mn, and Pb discovered, the intensity of PL dropped by 5.7%, 14.2%, and 21.4%, respectively. Among these various heavy metal ions, Pb ions show the most affected by the quenching effect in Cdots-based photoluminescence, FTIR, and ultraviolet-visible light absorption characterization. Based on the results of three heavy metal ion experiments, this study can be implemented as the heavy metal ion sensor-based luminescence quenching effect of Cdots.